2005
DOI: 10.1111/j.1600-6143.2005.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Late Antibody‐Mediated Rejection 30 Years After a Living‐Related Renal Allograft

Abstract: Antibody-mediated renal allograft rejection has become increasingly recognized and more clearly defined through the use of flow cytometry cross-matching and the deposition of C4d in renal allograft biopsies. All of the cases reported thus far have developed an antibody within 10 years of transplantation, and many lacked HLA and/or donor specificity.The present patient developed an anti-HLA donorspecific antibody between the 22nd and 30th year after a living-related renal transplant. At the 30th year posttransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…HLA antibodies have even been detected as much as 30 years after transplantation, resulting in compromise of renal function (13). Similar association of posttransplant antibodies with rejection of heart and lung transplants have been extensively summarized by Reinsmoen et al (14).…”
Section: Discussionmentioning
confidence: 75%
“…HLA antibodies have even been detected as much as 30 years after transplantation, resulting in compromise of renal function (13). Similar association of posttransplant antibodies with rejection of heart and lung transplants have been extensively summarized by Reinsmoen et al (14).…”
Section: Discussionmentioning
confidence: 75%
“…Already 25 years ago, Tosi et al demonstrated the presence of antibodies binding to the ␣-subunit of what were then called DC antigens (now known as DQ [3]). Weinstein et al [4] reported on a patient developing donor-specific antibodies (DSA) 30 years post-transplantation specific to HLA-A11. Upon further investigation it was found that additional DSA were generated against the donor QDA1*0501 chain.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the risk of humoral rejection exists at any time after RTx. In a recent study, one patient developed an anti‐HLA donor‐specific Ab between the 22nd and 30th year after LRKT and experienced AMR [26]. Therefore, we consider that long‐term monitoring for anti‐HLA Abs is necessary.…”
Section: Discussionmentioning
confidence: 99%